Are peptidomimetics the compounds of choice for developing new modulators of the JAK-STAT pathway? - Cugudda, Alessia; La Manna, Sara; Marasco, Daniela (Frontiers in Immunology, 2024)
Protein-protein interactions (PPIs) play critical roles in a wide range of biological processes including the dysregulation of cellular pathways leading to the loss of cell function, which in turn leads to diseases. The dysfunction of several signaling pathways is linked to the insurgence of pathological processes such as inflammation, cancer development and neurodegeneration. Thus, there is an urgent need for novel chemical modulators of dysregulated PPIs to drive progress in targeted therapies. Several PPIs have been targeted by bioactive compounds, and, often, to properly cover interacting protein regions and improve the biological activities of modulators, a particular focus concerns the employment of macrocycles as proteomimetics. Indeed, for their physicochemical properties, they occupy an intermediate space between small organic molecules and macromolecular proteins and are prominent in the drug discovery process. Peptide macrocycles can modulate fundamental biological mechanisms and here we will focus on peptidomimetics active on the Janus kinase /signal transducers and activators of transcription (JAK-STAT) pathways.